Analisis Pengaruh Penempatan Kerja Terhadap Turnover Intention: Peran Beban Kerja Sebagai Variabel Mediasi di Kalangan Pekerja Gen-Z Kota Pontianak - Muhamad Wanda Irfan Maulana; Sunardi Ginting (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study explores the influence of job placement and workload on Generation Z employees' intention to leave their jobs, with a focus on the unique characteristics of this emerging demographic in the workforce.A quantitative approach was employed, with 209 respondents from diverse industry sectors completing a questionnaire. The data was processed using Warp PLS 8.0 software and the Structural Equation Model (SEM) Approach Method to determine the relationship between job placement and turnover intention, with workload serving as a mediating variable. The findings indicate that high turnover intention is predominantly driven by substantial workload, which functions as a mediating variable.This phenomenon is also influenced by job placement interest and competence, though the influence is not substantial.The study underscores the significance of appropriately assigning workers to preserve Generation Z skills and effectively manage workload. The objective of this study is to assist businesses in reducing turnover intention among young workers by offering insights into the influence of job placement and workload on turnover intention.